Resposta espectral da cultura do feijão em condição de déficit hídrico - Silva, Guilherme Fernando Capristo (2015)
The use and management of irrigation techniques are intended to ensure an adequate water supply to plants, and techniques that in addition to increasing productivity, tend to promote an improvement in the quality of the final product. All vegetation with high state of water stress tends to absorb less solar radiation, causing an increase in reflectance in the visible spectrum and absorbing more near infrared. Thus, the objective of this work is to study the effects of water stress in bean arising from changes in water management, and detect stress by using digital camera and vegetation indices. The work was conducted in greenhouse using of plastic vessels to compose experimental plots sown with the bean cultivar IPR Tangara. The humidity of experimental plots was monitored using TDR unit and were maintained close to field capacity (FC), but when arrivals phenological phases predetermined were kept close to the wilting point (PMP), and past each phenological stage, irrigation is returning to try and keep the soil moisture close to DC by the end of the cycle. The acquisition and processing of images were performed by using a digital camera Fujifilm IS Pro® 5 UVIR, and the computer program IDRISI Selva® with CTVI vegetation indices, EVI, GNDVI and NDVI. The treatments consisted of T1: water stress in V4 stage; T2: water stress in the R6 stage; T3: water stress at R7 stage; T4: water stress in the stadium R8; T5: water stress in R9 stadium; T6: no stress around cycle; T7: with stress in every cycle. For the statistical analysis of variables NVP, NGP, MSPA, ALT, MCG, PROD was carried out ANOVA and comparison of means by t test (LSD) at 5% level of significance by the computer program SISVAR®. Likewise, it was conducted for comparison between the water with and without stress conditions in each phenological stage among the vegetation indices used. Comparing the vegetation index and water conditions with and without stress throughout the cycle, and stress in a developmental stage during the cycle the Shapiro-Wilk and Hartley tests that checks the normality and homogeneity of variance were used. When these assumptions are met, it was applied to regression analysis to test at 0,05 significance F. different water management conditions in the soil directly influenced components in the production evaluated, except for the mass hundredfold. Identify water conditions with and without stress at each developmental stage in bean crop was possible to use digital photographic images processed with GNDVI and NDVI. Regarding the identification of water conditions with and without stress over the cycle and water stress in one phenological stage in the bean crop it was possible to use the EVI vegetation indices and NDVI respectively.